Correlation of TOPS Score with the Short-term Outcome of Transported Neonates: An Experience from Resource-limited Settings: A Prospective Observational Study - Rajkumar Meshram; Ranjeet Chatnalkar (Mashhad University of Medical Sciences, 2022)
Background: Acute derangements of neonatal physiological parameters, such as temperature, oxygen saturation, skin perfusion, and blood sugar (TOPS parameters), can adversely affect the neonatal outcome. To correlate the TOPS parameter with the short-term outcome of transported neonates. Methods: This prospective observational study was carried out on 300 transported neonates by applying TOPS parameters within an hour of admission, and the outcome was assessed after 72 h of hospitalization. Results: Hypothermia, hypoxemia, hypoperfusion, and hypoglycemia were found in 37%, 30%, 32%, and 13.33% of the neonates, respectively. The neonatal mortality rate was obtained at 20.67%. Among the non-survivors, hypoxemia was the most prevalent abnormality, followed by hypoperfusion in 77.42% of the neonates. All the neonates with all normal parameters (score 0) survived, while those with all abnormal parameters (score 4) showed 100% mortality. It was observed that an increase in the score led to an increase in the mortality rate, and it was statistically significant (P=0.001). The overall sensitivity and specificity were estimated at 87.1% and 84.03%, respectively, with a positive predictive value of 58.7% and a negative predictive value of 96.15%. The area under the receiver operating characteristic curve was 0.913 when the TOPS score was ≥ 2. The prediction of mortality was most sensitive with hypoxemia, followed by hypoperfusion, with sensitivities of 82.26% and 77.42% and negative predictive values of 94.76% and 93.14%, respectively. Conclusion: The TOPS score was a reliable tool to predict mortality in transported neonates as mortality significantly increased by an increase in the TOPS score. Mortality was high when the scores of all four parameters were abnormal, while there was a better chance of survival with a score of zero.